The Fairy Tale Enchantment and Metamorphoses in Fay Weldon’s Novel The Life and Loves of a She-Devil - Golban, Tatiana; Karip, Özge (Border Crossing, 2017)
This article focuses on enchantment and metamorphoses motifs as used by Fay Weldon in her work The Life and Loves of a She-Devil. Since the encounter with magic is frequently stimulated by the human’s desire for more, the novelist explores these possibilities in order to represent the protagonists’ quest for the self. This study aims at discussing the protagonists’ encounter with marvellous and the way it triggers the process of metamorphoses. The transformation affects primarily the protagonists’ personality, as in the process of enchantment he/she dares to disclose her/his own potential, of which he/she was unaware prior to the exposure to wonder. This article also tries to reveal how Fay Weldon uses and subverts the mechanisms of enchantment because of her awareness that the apparently inoffensive transformations can cause privilege or repression of an individual.